Cortical Alterations in Medication‐Overuse Headache. Issue 2 (28th December 2016) - Riederer, Franz; Schaer, Marie; Gantenbein, Andreas R.; Luechinger, Roger; Michels, Lars; Kaya, Marihan; Kollias, Spyridon; Sándor, Peter S.
Abstract : Objective: Using surface‐based morphometry we aimed to provide a detailed examination of cortical alterations in medication‐overuse headache (MOH), by disentangling between altered cortical thickness and gyrification (folding). Background: In MOH, pain modulation is probably dysfunctional at the cortical and subcortical level, resulting in a disequilibrium between pain inhibition and facilitation. Both increased and decreased cortical volumes have been reported in individuals with MOH. There is however no detailed examination to date that distinguishes between altered cortical thickness and gyrification. Such distinction would help to identify the nature and timing of neurodevelopmental mechanisms at play in affected individuals. Methods: We investigated cortical thickness and gyrification in 29 patients with MOH according to International Headache Society criteria and 29 age‐ and gender‐matched controls, using high‐resolution structural MRIs of the brain analyzed with FreeSurfer. This is a secondary analysis of data from a previously published voxel‐based morphometry study. Results: In patients with MOH compared to controls, reduced cortical thickness was observed in the left prefrontal cortex. We also observed higher local gyrification in one cluster extending from the fusiform cortex to adjacent medial temporal regions, and in another cluster in the right occipital pole. Higher gyrification in the right occipital pole predicted poor response after detoxification. Conclusions: Corroborating previous volumetric results, our study adds information on the putative neurobiological mechanisms involved in MOH, suggesting neurodevelopmental changes in MOH.